Uma abordagem fuzzy para o desempenho escolar no processo ensino-aprendizagem - Silva, Gustavo Cavani Teles da (Universidade Federal de São Carlos, 2023)
Assessing the teaching-learning process and measuring student development can be a complex and subjective task. Therefore, Fuzzy Set Theory is a distinctive tool for this process. From this perspective, this work aims to study basic concepts of Fuzzy Set Theory and an application of this study by proposing a mathematical model to assist teachers in the task of evaluating students’ learning via fuzzy relational equations.
A fuzzy approach to school performance in the teaching-learning process
Keywords: Avaliação; Conjuntos Fuzzy; Relações Fuzzy; Assessment; Fuzzy Sets; Fuzzy Relations; CIENCIAS EXATAS E DA TERRA::MATEMATICA